Super‐Robust Xanthine–Sodium Complexes on Au(111). (23rd February 2022) - Chen, Chong; Ding, Pengcheng C.; Li, Zhuo; Shi, Guoqiang Q.; Sun, Ye; Kantorovich, Lev N.; Besenbacher, Flemming; Yu, Miao
Abstract: A widely accepted theory is that life originated from the hydrothermal environment in the primordial ocean. Nevertheless, the low desorption temperature from inorganic substrates and the fragileness of hydrogen‐bonded nucleobases do not support the required thermal stability in such an environment. Herein, we report the super‐robust complexes of xanthine, one of the precursors for the primitive nucleic acids, with Na. We demonstrate that the well‐defined xanthine–Na complexes can only form when the temperature is ≥430 K, and the complexes keep adsorbed even at ≈720 K, presenting as the most thermally stable organic polymer ever reported on Au(111). This work not only justifies the necessity of high‐temperature, Na‐rich environment for the prebiotic biosynthesis but also reveals the robustness of the xanthine–Na complexes upon the harsh environment. Moreover, the complexes can induce significant electron transfer with the metal as inert as Au and hence lift the Au atoms up. Abstract : By mimicking the prebiotic submarine synthesis with a simplified model, i.e. reaction of xanthine and NaCl on Au(111), the necessity and appropriateness of high‐temperature, Na‐rich environment for the prebiotic biosynthesis is justified, by demonstrating that xanthine can form well‐defined complexes with Na, but only at a temperature ≥430 K, and that the complexes are super‐robust and remain adsorbed on Au(111) at a temperature as high as 720 K.